2018
DOI: 10.1111/1753-0407.12879
|View full text |Cite
|
Sign up to set email alerts
|

Association of common type 1 and type 2 diabetes gene variants with latent autoimmune diabetes in adults: A meta‐analysis

Abstract: Background The aim of this meta‐analysis was to determine the association of common type 1 diabetes (T1D) and type 2 diabetes (T2D) gene variants (protein tyrosine phosphatase non‐receptor 22 [PTPN22] rs2476601C/T, insulin [INS] rs689A/T and transcription factor 7‐like 2 [TCF7L2] rs7903146C/T) with latent autoimmune diabetes in adults (LADA). Methods A systematic search of electronic databases was conducted up to 2017 and data from 16 independent case‐control studies for three gene variants were pooled. The po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…The risk of LADA is substantially increased with family history of T1D disease but also, albeit significantly less so, of T2D disease (36). A meta-analysis from 16 independent case-control studies (8,869 cases and 20,829 controls total), aimed at determining the association of T1D and T2D gene variants, demonstrated that some of these polymorphisms are associated with the risk of LADA, further supporting the idea of LADA as a combination of both T1D and T2D and emphasizing its heterogeneity (37). The first genome-wide association study of LADA revealed how the leading genetic signals were principally shared with T1D, although positive genetic correlations genome-wide were registered also with T2D.…”
Section: Lada At the Intersection Of Type 1 And Type 2 Diabetesmentioning
confidence: 93%
“…The risk of LADA is substantially increased with family history of T1D disease but also, albeit significantly less so, of T2D disease (36). A meta-analysis from 16 independent case-control studies (8,869 cases and 20,829 controls total), aimed at determining the association of T1D and T2D gene variants, demonstrated that some of these polymorphisms are associated with the risk of LADA, further supporting the idea of LADA as a combination of both T1D and T2D and emphasizing its heterogeneity (37). The first genome-wide association study of LADA revealed how the leading genetic signals were principally shared with T1D, although positive genetic correlations genome-wide were registered also with T2D.…”
Section: Lada At the Intersection Of Type 1 And Type 2 Diabetesmentioning
confidence: 93%
“…The T allele was associated with a reduced risk of T1DM, but was not associated with the risk of LADA. In their meta-analysis, Ramu et al ( 22 ) also showed an inverse association between LADA and the presence of the T allele in the codominant, dominant and recessive models.…”
Section: Discussionmentioning
confidence: 95%
“…Interestingly, there was a 30-year difference in the mean age of diagnosis between the groups. In their 2019 meta-analysis, Ramu et al ( 22 ) also compared subjects with LADA and healthy controls, and reported a significant association for the risk allele in rs2476601 with LADA in the codominant, dominant and recessive models.…”
Section: Discussionmentioning
confidence: 99%
“…These SNPs include the common rs3842752, located in the three prime untraslated region (3’ UTR) of the INS mRNA and potentially causing mRNA instability [ 17 ], and rs689 located in an intron splice-site [ 15 , 18 , 19 , 20 ]. In addition to T1D, rs689 has been shown to associate with T2D [ 21 , 22 ] and the relatively prevalent diabetes subtype, latent autoimmune diabetes of adulthood (LADA) [ 23 , 24 ], which resembles the autoimmune nature of T1D and the metabolic profile of T2D [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%